Leadership 2.0 - Bradberry, Travis (United State of America : Talensmart, 2012)
Introduces the concept of "Adaptive Leadership Skills," the skills pinpointed to be the most effective and helps readers determine which they need to work on most in order to improve leadership ability.
Keywords: Leadership. Leadership; Social aspects